การบริหารจัดการทางการพยาบาลในสถานการณ์ การแพร่ระบาดของโควิด 19 โรงพยาบาลสมุทรปราการ - อารีย์วรรณ อ่วมตานี (สมาคมพยาบาลทหารบก, 2022)
This study was to develop and use a clinical nursing practice guideline (CNPG) for Coronavirus 2019 (COVID-19) patients and evaluate the feasibility of implementation of the CNPG for the patients infected with COVID-19 in cohort intensive care unit at a tertiary hospital in Metropolitan, Bangkok. The sample was 18 registered nurses who work with patients infected with COVID-19. The National Health and Medical Research Council Model was used to develop the CNPG. The research tools were composed of: 1) the developed clinical nursing practice guideline about oxygen therapy for the patients infected with COVID-19, 2) a focus group questionnaire, 3) in-depth- interview questionnaire, and 4) the feasibility of the CNPG questionnaire. The results are as follows: 1) The developed clinical nursing practice guideline for the patients Infected with COVID-19 in the Critical Cohort Department consisted of 3 components as follows: 1) need assessment for intubation tube, 2) hypoxia assessment, 3) monitoring clinical signs and symptom. The results of applying found that the Feasibility of the clinical nursing practice guideline was at a high level (x̅ = 2.66, SD. = 0.32) and there was no incidence of registered nurses in the cohort intensive care unit infected with COVID-19. Therefore, it can be further used as the CNPG in the cohort intensive care unit for the prevention of COVID-19 infection for a long time to investigate about the sustainability of CNPG use.